Встановлення квазібінарних перерізів у потрійній взаємній системі Tl2Se+SnTe↔Tl2Te+SnSe - Філеп Михайло; Filep Mykhailo; Filep Mihály; Малаховська Тетяна; Malakhovska Tetyana; Погодін Артем; Pogodin Artem; Сабов Мар’ян; Sabov Marjan; Szabó Marján (ДВНЗ Ужгородський національний університет, 2019)
Резюме. Бінарний телурид SnТe відноситься до класичних легуючих домішок для термоелектричних матеріалів [1], а селенід SnSe – характеризується одним із найвищих показників термоелектричної добротності [2]. Тернарні сполуки типу Tl4SnX3 (X – Se, Te) володіють низькою фононною теплопровідністю та високими значеннями термоелектричної добротності ZT [3, 4]. Це обумовлює можливість їх використання у якості термоелектричних елементів. Для розширення області використання перспективних матеріалів проводяться чисельні дослідження фізико-хімічної взаємодії систем за участю фаз SnX та Tl4SnX3 (X – Se, Te) [5-7]. Метою даної роботи є встановлення квазібінарних перерізів потрійної взаємної системи Tl2Se+SnTe↔Tl2Te+SnSe.

Abstract. The compounds of Tl4SnX3 (X – Se, Te) formula show low thermal conductivity and relatively high thermoelectric figure of merit ZT. Therefore compounds Tl4SnX3 can be used as perspective materials for thermoelectric devices. To increase the scope of use an investigation of the physicochemical interaction in the systems based on the compounds Tl4SnX3 is promising. The Tl4SnX3 compounds are formed in the in quaternary Tl–Sn–Se–Te system and could be presented as ternary reciprocal system Tl2Se+SnTe↔Tl2Te+SnSe. The binary phases Tl2Se, Tl2Te, SnSe and SnTe, which are located in the corners of concentration quadrangle, melts congruently. The compound SnSe have a polymorphic transformation at 807 K. The Tl2Se–Tl2Te and SnSe–SnTe quasi binary sections refer to the eutectic type system. The quasi binary section Tl2Se–SnSe and Tl2Te–SnTe are characterized by the formation of several congruently melting ternary compounds: Tl4SnSe3 (706 K) and Tl4SnTe3 (817 K); and incongruently melting compound Tl2Sn2Se3 (683 K). The Tl2Sn2Se3 compound exists only in narrow temperature range (640–683 K), because of solid-state decomposing and its crystal structure is unknown. The ternary Tl4SnSe3 and Tl4SnTe3 have a wide homogeneity area. The existences of quaternary compound Tl2SnSeTe are not confirmed. Since the determinations of quasi binary sections are carried out below the temperature interval of the existence of the Tl2Sn2Se3 phase, it was not taken into account in further investigations. Thus, the concentration quadrangle of the Tl2Se+SnTe↔Tl2Te+SnSe system is characterized by the presence of 4 binary phases (at vertices) and two ternary phases (on the sides). This occurs that the Tl2Se+SnTe↔Tl2Te+SnSe system will be divided by three quasi binary sections on four quasi ternary systems. Inside one of them the partially quasi binary section, based on the incongruently melting phase Tl2Sn2Se3, will be realized. All possible sections intersect at 9 points. For determination of the quasi binary sections the experimental method was, which consists in investigation of the phase compositions of the alloy, which are at the intersection of possible quasi binary sections. The binary compounds were synthesized using high purity (99.99% mas.) elemental components. The ternary compounds and investigated alloys were obtained using the pre-synthesized binary compounds by one temperature method. All synthesized alloys were investigated by DTA, XRD and MSA analysis. Used the XRD method existence of three quasi binary sections Tl4SnSе3–Tl4SnTе3 Tl2Sе– Tl4SnTе3 and SnSе–Tl4SnTе3 were determined.
Determination of the quasi binary sections in the ternary reciprocal system Tl2Se+SnTe↔Tl2Te+SnSe
Keywords: халькогеніди; квазібінарний переріз